FACTORS INFLUENCING MENSTRUAL HYGIENE PRACTICE AMONG ADOLESCENT GIRLS - Luvi Dian Afriyani; Eti Salafas (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Adolescents were classified as a healthy group and far from risk factors for illness, but most health problems can occur due to their poor behavior. Menstruation is a sign of adulthood. When menstruation came, the vagina becomes moister, and it increases the risk to stimulates fungus and bacteria to grow. That why menstrual hygiene is important to suppress the occurrence of infection.The purpose of this study is to determine the factors that influencemenstrual hygiene practice in adolescents. A survey method conducted on 82 students from seven and eight grade using a purposive sampling technique. Collected data analyzed by using logistic regression.The results showed thatfactors related to menstrual hygiene practice were knowledge (p-value: 0.002) and family (p-value: 0.004), while unrelated factors were friend (p-value: 0.07) and media (p-value; 0.1) Based on the logistic regression test, the knowledge factor is the most influential (p-value; 0.006 and Exp (B): 4.07) It is recommended to do health promotion regarding menstrual hygiene practices through collaboration with health services. Key Words : Practice, Mestrual Hygiene, Adolescent